Reading Between the Lines: Revealing Interiority - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2020)
Words, texts and narratives have the potential to reveal the complexity of interiority; they can tell stories beyond the physical materiality of space to reveal spatial occupation, address social and cultural issues embedded in space and capture the trajectories of inhabitation over time. This issue of Interiority addresses writing and reading as a form of inquiry towards the idea of interiority being embedded within the represented forms of architecture and interior. The articles in this issue demonstrate various forms of inquiry concerning the idea of interiority through various media of ‘writing,’ then explore how their reading becomes a way of revealing interiority.